2004
DOI: 10.1121/1.1784437
|View full text |Cite
|
Sign up to set email alerts
|

Informational masking in hearing-impaired and normal-hearing listeners: Sensation level and decision weights

Abstract: Informational masking (IM) refers to elevations in signal threshold caused by masker uncertainty. The purpose of this study was to investigate two factors expected to influence IM in hearing-impaired listeners. Masked thresholds for a 2000-Hz signal in the presence of simultaneous multitone maskers were measured in 16 normal-hearing (NH) and 9 hearing-impaired (HI) listeners. The maskers were 70 dB SPL average total power and were comprised of fixed-frequency components between 522 and 8346 Hz that were separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 33 publications
3
75
1
Order By: Relevance
“…Multiple logistic regression (PROC LOGISTIC, SAS 9.2) was used to estimate the influence of the level of each individual temporal segment on the response of the listener (see Agresti, 2002;Alexander & Lutfi, 2004;Oberfeld, 2008a;Pedersen & Ellermeier, 2008). 2 The binary responses served as the dependent variable, and the 10 or 13 segment levels served as predictors, which were entered simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple logistic regression (PROC LOGISTIC, SAS 9.2) was used to estimate the influence of the level of each individual temporal segment on the response of the listener (see Agresti, 2002;Alexander & Lutfi, 2004;Oberfeld, 2008a;Pedersen & Ellermeier, 2008). 2 The binary responses served as the dependent variable, and the 10 or 13 segment levels served as predictors, which were entered simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of simultaneous masking have shown large detrimental effects of masker-frequency uncertainty, often created by randomizing the frequency content of a multi-tonal masker each time it is presented ͑e.g., Watson et al, 1975;Neff and Green, 1987;Kidd et al, 1994;Oh and Lutfi, 1998;Alexander and Lutfi, 2004;Richards and Neff, 2004;Durlach et al, 2005͒. For example, simultaneous-masking studies with fixed-frequency sinusoidal signals and randomfrequency multi-tonal maskers have reported as much as 50 dB of masking for trained listeners ͑e.g., Neff and Green, 1987͒.…”
Section: Introductionmentioning
confidence: 99%
“…Results from early studies of informational masking ͑e.g., Watson et al, 1976;Spiegel et al, 1981;Neff and Green, 1987͒ were interpreted as indicating that listeners were not able to attend only to information in the signal frequency region. Consistent with this explanation, Lutfi and colleagues ͑e.g., Lutfi, 1993;Lutfi a͒ et al, 2003, Alexander andLutfi, 2004͒ modeled informational masking in terms of the number and frequency range of auditory filters monitored when a listener is asked to detect a tonal signal at a fixed frequency in the presence of a random-frequency, multi-tonal masker. In that approach, data with little evidence of informational masking were modeled as resulting from a highly frequency-selective process, characterized in terms of a very narrow attentional filter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berg 1990;Lutfi 1995;Richards 2002). Studies using this paradigm show listeners to have highly replicable, individualistic patterns of decision weights on frequencies affecting their ability to hear out specific targets in noise-what has been referred to as individual listening styles (Doherty and Lutfi 1996;Lutfi and Liu 2007;Jesteadt et al 2014;Alexander and Lutfi 2004). Unfortunately this paradigm is extremely time-consuming, rendering it ineffective for clinical use.…”
Section: Introductionmentioning
confidence: 99%